How do law enforcement agencies recruit diverse applicants? Analysis of digital recruiting materials - Rineer, Jennifer R (International journal of police science & management, 2023)
Law enforcement agencies across the country are struggling to recruit qualified candidates and this problem is pronounced when recruiting demographically diverse officers. Women demonstrate competencies important for effective policing: restoring trust in police, obtaining high case clearance rates, and using less force. The goal of this study was to understand how agencies use online recruiting materials to recruit women officers. We assessed the frequency of text, images, and videos depicting women and racially and ethnically diverse individuals, and content related to hiring and the job itself. We conducted thematic analysis to understand how policing, the agency, and diversity were portrayed. Characteristics known to discourage women applicants were highlighted prominently in materials. Agencies did not provide consistent messaging about diversity, resources for women, or support for work–life balance. We found differences between agencies with higher and lower percentages of women, but they were inconsistent and often in unexpected directions.